PENGARUH LEADER MEMBER EXCHANGE (LMX), DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP LOYALITAS PEGAWAI LPP RRI MADIUN - Setiaji, Rohmad Dwi; Farida, Umi; Purwaningrum, Titis (ANALISIS, 2024)
"This research was conducted to partially and simultaneously observe whether leader member exchange, work discipline, and work motivation influence the loyalty of employees at LPP RRI Madiun. This is because in today's digital era, the role of radio has started to lag behind other mass media. In order to remain competitive, employee loyalty in the company must be improved to achieve this goal. The population in this study is all employees of LPP RRI Madiun, totaling 64 employees. The technique uses a nonprobability sampling method with a saturated sampling technique (census). The data source applies primary data through the use of a questionnaire instrument. The testing of data quality analysis applies validity and reliability tests. The testing of constant and unbiased regression results applies the classic assumption test. Hypothesis testing applies the partial regression coefficient test (t-test) and simultaneously (f-test). It can be concluded that the partial test (t) consisting of independent variables Leader Member Exchange (X1) = 3.019, Work Discipline (X2) = 4.412, Work Motivation (X3) = 3.243, simultaneously (f), the three independent variables simultaneously influence Employee Loyalty (Y) by 103.725. This research proves that leader member exchange, work discipline, and work motivation are significant factors influencing employee loyalty. Of the three independent variables, work discipline has the greatest influence on employee loyalty, followed by work motivation and leader member exchange. Therefore, the researcher recommends that leaders and employees improve the quality of work relationships, discipline, and work motivation to create high employee loyalty.